Pengaruh Flipped Classroom Beraktivitas Gamifikasi Tradisional Terhadap Self Regulated Learning Pada Pembelajaran Pemrograman Visual - Hadihabibi, Moh; Setyosari, Punaji; Soepriyanto, Yerry (Universitas Negeri Malang, 2023)
Learning visual programming requires a strategy that is effective and motivates students. Flipped classroom with gamification activities can be a solution to this problem. Gamification is characterized by the use of game elements in a non-game context that aims to engage and motivate students. The implementation of gamification in this study was done traditionally. In order for learning in the classroom to focus on gamification activities in a traditional way, an activity before entering the classroom is needed in the form of an activity to review learning materials called a flipped classroom. In flipped classroom, students must have self-regulated learning skills in order to achieve academic success. Therefore, the purpose of this study is to explain the difference in self-regulated learning between flipped classroom with gamification activities and flipped classroom without gamification. This research is a quasi-experimental quantitative research. The results showed that there is a difference in self-regulated learning between flipped classroom learning with gamification activities and flipped classroom learning without gamification. Other findings showed that gamified flipped classroom learning received positive responses from students. Therefore, learning using flipped classroom with gamification activities can be applied in visual programming learning, especially to generate student learning motivation.AbstrakDalam pembelajaran pemrograman visual diperlukan sebuah strategi yang efektif serta membangkitkan motivasi belajar siswa. Flipped classroom beraktivitas gamifikasi dapat dijadikan solusi dalam permasalahan tersebut. Gamifikasi ditandai dengan penggunaan unsur-unsur permainan dalam konteks yang bukan permainan yang bertujuan untuk melibatkan dan memotivasi siswa. Penerapan gamifikasi dalam penelitian ini dilakukan secara tradisional. Agar pembelajaran di dalam kelas berfokus pada kegiatan gemifikasi secara tradisional, diperlukan kegiatan sebelum memasuki kelas berupa aktivitas meninjau materi pembelajaran yang disebut flipped classroom. Dalam flipped classroom siswa harus memiliki keterampilan self regulated learning agar mencapai keberhasilan akademik. Oleh sebab itu tujuan dalam penelitian ini adalah menjelaskan perbedaan self regulated learning antara flipped classroom beraktivitas gamifikasi dengan flipped classroom tanpa gamifikasi. Penelitian ini termasuk penelitian kuantitatif kuasi eksperimen. Hasil penelitian menunjukkan bahwa terdapat perbedaan self regulated learning antara pembelajaran flipped classroom beraktivitas gamifikasi dengan pembelajaran flipped classroom tanpa gamifikasi. Temuan lain menunjukkan pembelajaran gamified flipped classroom mendapat respon yang positif dari mahasiswa. Oleh sebab itu pembelajaran dengan menggunakan flipped classroom beraktivitas gamifikasi dapat diterapkan dalam pembelajaran pemrograman visual khususnya untuk membangkitkan motivasi belajar siswa.